Preparation, Characterization, and In Vitro Performance of Gambogic Acid-Layered Double Hydroxide/Liposome Nanocomposites - Xiaoyan Han; Qi Liu; Rou Zhao; Shan Wang; Yi Zhang (Journal of Chemistry)
Gambogic acid (GA) refers to a xanthonoid that exhibits significant antitumor activity due to its poor solubility and low bioavailability. For this reason, its shortcoming should be overcome using novel approaches to improve its practical effectiveness. In this study, with the use of ion exchange method, GA was encapsulated in layered double hydroxide (LDH). In the GA-LDH nanohybrid, GA was distributed and stabilized in the interlamellar region of LDH through intermolecular interactions. GA-LDH was further modified by liposome (LS) through ethanol injection method. The drug encapsulation efficiency of GA-LDH/LS was obtained as 56.28%. The chemical structures and physicochemical properties exhibited by GA-LDH/LS were characterized and confirmed using different instruments, and drug release showed that GA-LDH/LS had significantly sustained release due to the combined effect of the matrix LDH and the phospholipid bilayer. Furthermore, GA-LDH/LS displayed lower hemolysis percentage than GA-LDH during the hemolysis test. This study suggested that GA-LDH/LS nanocomposite could be a promising antitumor drug delivery system due to its outstanding performance in biomedical research.